Body Composition and Associations with Muscle Strength in Older Adults Living in Auckland, New Zealand - Anne N. Hiol; Pamela R. von Hurst; Cathryn A. Conlon; Kathryn L. Beck (Proceedings, 2020)
Objectives: To investigate associations between body composition and muscle strength in older [...]